Empathy among healthcare workers in the context of patient dying and death – a narrative review - Polanowska, Marta; Krzeminska, Sylwia (Journal of Education, Health and Sport, 2026)
Introduction: Empathy is a fundamental component of high‑quality care for patients at the end of life. In interactions with dying individuals and their families, healthcare workers navigate both professional responsibilities and emotional involvement, which shapes the quality of the care they provide. Narrative Review: This review synthesizes research examining empathy among various groups of healthcare professionals, including nurses, physicians, medical caregivers, students, and community care workers. The overview identifies factors that strengthen or diminish empathy, explores strategies used by professionals to cope with patient death, and highlights the importance of organizational support. The reviewed studies underline the complexity of empathy as both an emotional response and a clinical competency. Conclusions: The literature demonstrates that empathy is a dynamic, multifaceted construct influenced by personal characteristics, workplace conditions, and broader organizational structures. Strengthening empathy requires comprehensive support for healthcare workers, the development of advanced communication skills, and institutional strategies that promote resilience and compassionate care.